77 International collaboration between Uganda and the UK to design Sub-Saharan Africa's first Palliative Care Fellowship programme: mutual benefits and learning. (14th March 2023) - Howorth, Kate; Namukwaya, Elizabeth; McGeough, Kathleen; Snell, Kalyani; Ikong, Hannah; Leng, Mhoira
Abstract : Background: 80% of people with severe health-related suffering live in low and middle income countries, such as Uganda. This burden is predicted to increase rapidly. One of the main barriers to global Palliative Care (PC) availability is a lack of training, particularly of senior healthcare professionals to lead teams, support services, and influence policy. There is currently no accredited PC sub-speciality training for graduate doctors in Sub-Saharan Africa, compared to a well-established UK training programme with recent curriculum development. Aim: The project aims to develop a Fellowship programme to allow doctors in Uganda, and later East Africa, to become senior clinical leaders with sub-specialty accreditation in PC through combining expertise and experience of UK and Ugandan colleagues. Methods: The project was led by a Ugandan physician with extensive PC experience and a UK specialist registrar volunteering in Uganda, with oversight from a consultant who had developed PC services internationally. They brought together a steering group of Ugandan physicians with PC experience and UK and Ireland consultants with understanding of PC in an African context and postgraduate education, who had regular virtual meetings to share ideas and make decisions. Results: The project leaders reviewed international curriculums and applied Bologna medical education principles to produce a competency-based curriculum, with contributions from volunteers via an APM bulletin. They wrote a Fellowship programme proposal which is being reviewed by the steering group and international experts, prior to submission for accreditation initially by Makerere University, Uganda. Conclusions: Collaboration between international colleagues allowed the sharing of expertise, resources, and experience from different settings to produce a Fellowship curriculum and programme grounded in medical education principles and applicable to the local context. This project provided an opportunity for cross-cultural learning, leadership development, growth of a network for senior PC teaching and mentoring, and possibilities for future partnerships.